RANCANG BANGUN REST WEB SERVICE HOTEL UNTUK MENINGKATKAN LAYANAN PARIWISATA SEMARANG (STUDI KASUS PADA HOTEL SEMESTA SEMARANG) (Information Technology and Telematics, 2013)
Abstract-- This study examines the exchange of  data between  Semesta  Hotel  Semarang  Website with  Semarang Tourism Website using web service  applications with REST protocol.  The  problem  is   how  to  make  a  web  service applications  that  can  share  information  between  Semesta Hotel Semarang Website with Tourism Website Semarang, so that  users   in  Semarang  Tourism  Website  can  also  see information held Semesta Hotel Semarang Website. The  study  produced  a  web  application  service  with REST protocol that has a function - a function  that can be used to share data between Semesta Hotel Semarang Website with Semarang Tourism Website. Through this system is expected to hopefully  Semesta Hotel Semarang can get more customers by  displaying its tourism  packet  data  in  Semarang  Tourism  Website.  For future improvement, complement and extend the functionality of the web service to plan the next steps. Keywords:    Web    Service,    REST,    Semesta    Hotel   Semarang